The Role of Principal Academic Supervision in Optimizing Independent Curriculum Implementation - Dewi, Desy Eka Citra; Nurniswah; Nurhikmah; Lubis, Elfahmi (JTP - Jurnal Teknologi Pendidikan, 2025)
The Independent Curriculum aims to improve students' learning outcomes in numeracy, literacy and emphasizes the development of 21st century competencies which include critical thinking skills, creativity, collaboration, communication, and the ability to learn independently, but the implementation of the Independent Curriculum, junior high school level in Bengkulu City, is still limited this is due to the uneven understanding of teachers, there are still many teachers who have difficulty in understanding the concept of the independent curriculum. In order for teachers to be able to apply the concept of the independent curriculum optimally, effective guidance, support and monitoring are needed from the principal through academic supervision. This study aims to analyze the form of academic supervision of the principal in implementing the independent curriculum in Junior High Schools in Bengkulu City. This type of research is a combination research (Mix Method) with a Sequential Explanatory Design model approach. The population and sample of the study used purposive sampling techniques. The study population was 159, namely teachers at Junior High School 5, Junior High School 18, Junior High School 24 and Junior High School 9 in Bengkulu City. The study was conducted for seven months (April - October 2023). Data collection techniques: observation, questionnaires, interviews and documentation. Data that has been collected in the form of questionnaires will be scored and analyzed using descriptive statistics, namely using the percentage formula (%), qualitative data is analyzed using the Miles and Huberman model. The results of the study confirmed that the principal's academic supervision has a strategic role in improving the implementation of the independent curriculum in junior high schools in Bengkulu City, the form of academic supervision of the principal in the implementation of the independent curriculum in junior high schools in Bengkulu City.